Effect of Sediment Particle Sizes on The Density and Morphometrics of Seagrass Enhalus acoroides Leaves at Pandaratan Beach Tapanuli Tengah - Banjarnahor, Novia; Samiaji, Joko; Nasution, Syafruddin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This study was conducted in March - May 2020 at Pandaratan Beach Tapanuli Tengah with the aims in observing the size of the sediment particles, the density of Enhalus acoroides, the morphometrics of seagrass leaves, and to analyze the effect of the average sediment particle size on the density and morphometrics of the seagrass leaves. The study used a survey method. Study stations were choosen by purposive sampling and the samples were observed by using a transect line method. The results showed that the particle size ranged from 0.097 - 0.364 mm. The highest density was at Station II with fine sand categories with a value of 37.89 stands/m2 and the lowest density was at Station I with medium sand sediment particles with a value of 25.44 stands/m2. The longest leaves was found at Station II with a value of 84.09 cm and the shortest was at Station I with a value of 65.93 cm. The widest leaves of E. acoroides was at Station II with a value of 1.92 cm and the narrowest was at Station I with a value of 1.81 cm. Simple linear regression test showed that effect of the sediment partikel size on the density and morphometrics of seagrass leaves